The performance of stone mastic asphalt incorporating iron ore - Al Gariri, Salem Mohammed Salem; Baqadeem, Abdullah Omar Abdullah; Moon, Lee Pei; Mazlan, Abu Seman; Khairil Azman, Masri (Horizon Research Publishing, 2023)
The high traffic load often appears for its resilient module and dynamic creep to affect the efficiency of the asphalt mixture. A typical way to resolve these problems is to change the properties of the asphalt binder by incorporating iron ore (IO) and stone mastic asphalt (SMA). Given that we use Iron ore to boost the asphalt properties in this research, this study aims to promote IO as an asphalt binder to strengthen asphalt mixture properties. This study aims to evaluate the mechanical performance of stone mastic asphalt 20 incorporating iron ore and to access the optimum iron ore content in the SMA. Iron ore is utilised to increase asphalt binding characteristics and ground paving performance. High freight weights, which increase road use owing to a variety of issues, including fatigue cracking and other deformations caused by stress on roadways, are one of the primary problems affecting thick-grade asphalted surfaces and quality performance. In this study, six different percentages of IO content were employed, which are as follows: (0%, 1%, 2%, 3%, 4%, and 5% from the total weight of aggregate). Furthermore, in this study, a 60/70 asphalt penetration grade was selected. The study compares modified and conventional bitumen specimens using the Marshall stability, resilient modular testing, dynamic creep, and LA abrasion tests. According to the results of this study, using a ranking of performance tests, the Optimum Iron Ores Content was determined to be 5 % iron ore. Therefore, we may conclude that there is improvement in incorporating additive IO into SMA.